Prevalensi Burnout Berdasarkan Jenis Kelamin pada Mahasiswa Fakultas Kedokteran Universitas Tarumanagara - Mulyono, Alya Dwiana; Yoseph Abdul Rahim, Alif (Ebers Papyrus, 2023)
Burnout is considered as a major issue experienced by medical students. Problems related to burnout have a higher degree of severity in medical students than students attending other study programs. Effects of burnout are known to have negative impact on performance and cognitive function on students. Thus, this research aims to identify prevalention of burnout in male and female medical students in Universitas Tarumanagara Class 2021 dan 2020. This descriptive qualitative study used convenient sampling method. Research instruments used in this study are Burnout Assessment Tool (BAT) to evaluate burnout. A total of 325 respondents from class of 2021 and 2022 participated in this study, which consisted of 232 (73.1%) female students and 93 (28.6%) male students. The result shows that a total of 180 (55.4%) respondents experienced burnout, out of which 134 (74.4%) were female respondents and 46 (25.6%) were male respondents.